2016
DOI: 10.1007/s11524-016-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Health Declines among African Americans in the USA

Abstract: The weathering hypothesis, an explanation for race disparities in the USA, asserts that the health of African Americans begin to deteriorate prematurely compared to whites as a consequence of long-term exposure to social and environmental risk factors. Using data from 2000-2009 National Health Interview Surveys (NHIS), we sought to describe differences in age-related health outcomes in 619,130 African Americans and whites. Outcome measures included hypertension, diabetes, stroke, and cardiovascular disease. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 59 publications
2
65
0
2
Order By: Relevance
“…While initially presented as an explanation for excess rates of infant mortality among black women, 3,4 it is now applied to explain broader disparities in health outcomes among disadvantaged populations. [5][6][7][8] Additional hypotheses, including normative differences in childbearing patterns by age, 9 allostatic load, 6,10-12 the developmental origins of health and disease, 13 and the life-course framework, 11,[14][15][16] have been developed to advance our understanding of disparities in birth outcomes. [16][17][18][19][20][21][22][23][24] The extent to which the various hypotheses apply to all minority women at all points in their reproductive lives is not clear.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…While initially presented as an explanation for excess rates of infant mortality among black women, 3,4 it is now applied to explain broader disparities in health outcomes among disadvantaged populations. [5][6][7][8] Additional hypotheses, including normative differences in childbearing patterns by age, 9 allostatic load, 6,10-12 the developmental origins of health and disease, 13 and the life-course framework, 11,[14][15][16] have been developed to advance our understanding of disparities in birth outcomes. [16][17][18][19][20][21][22][23][24] The extent to which the various hypotheses apply to all minority women at all points in their reproductive lives is not clear.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…This earlier and steeper health decline is conceptualised as a direct consequence of lifelong exposure to social and environmental disadvantage, which ultimately leads to widening health disparities between blacks and whites as they age. While initially presented as an explanation for excess rates of infant mortality among black women, it is now applied to explain broader disparities in health outcomes among disadvantaged populations …”
Section: Introductionmentioning
confidence: 99%
“…For example, Geronimus et al (2006) used data from the National Health and Nutrition Examination Survey (NHANES IV) to investigate whether young and middle-aged African Americans had a greater biological stress score as measured through 10 biomarkers (including blood pressure, body mass index, C-reactive protein, total cholesterol, among others) compared with Non-Hispanic Whites. They found that the mean biological stress score among African Americans was similar to that for Non-Hispanic Whites who were 10 years older, suggesting that stressors among African Americans led to accelerated aging (see also, Levine and Crimmins, 2014 , Thorpe et al, 2016 ). Thus, this hypothesis suggests that African Americans might have poorer cardiovascular, metabolic, and immune health.…”
Section: Introductionmentioning
confidence: 96%
“…Griffith and colleagues have highlighted the critical role that age or phase of life plays in relation to structures that shape Black men’s health in ways that foreground their efforts to embody positive and prosocial ideals of manhood ( Griffith, 2015 ; Griffith & Cornish, 2016 ; Griffith, Cornish, Bergner, Bruce, & Beech, 2017 ; Griffith, Cornish, McKissic, & Dean, 2016 ; Griffith et al, 2013 ; Griffith, Gunter, & Allen, 2011 ). Yet the stress of their engagement with educational, economic, social, and legal systems may drive the high rates of premature mortality and physiological aging that have become synonymous with Black men’s health ( Bruce, Griffith, & Thorpe Jr, 2015a ; Bruce, Griffith, & Thorpe Jr, 2015b ; Thorpe Jr, Duru, & Hill, 2015 ; Thorpe Jr & Kelley-Moore, 2013 ; Thorpe et al, 2016 ).…”
Section: Centering the Margins: The Promise Of Intersectionality In Mmentioning
confidence: 99%